2021
DOI: 10.2196/30249
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Academic Trends in Neuropsychological Tests for Executive Functions Using Virtual Reality: Systematic Literature Review

Abstract: Background In neuropsychology, fully immersive virtual reality (VR) has been spotlighted as a promising tool. It is considered that VR not only overcomes the existing limitation of neuropsychological tests but is also appropriate for treating executive functions (EFs) within activities of daily living (ADL) due to its high ecological validity. While fully immersive VR offers new possibilities of neuropsychological tests, there are few studies that overview the intellectual landscape and academic tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“…Previously, evidence has suggested the support of enhancing cognitive functioning in healthy older adults by using cognitive-based trainings (Gavelin et al, 2020;Sanjuán et al, 2020). Nevertheless, despite the diversity among applied cognitive interventions in healthy older adults, the VR-based intervention has not been widely adopted for boosting EFs (Kim et al, 2021). EFs (i.e., inhibitory control, WM, and attentional flexibility) has been linked with daily activities since these functions include the ability to evaluate, organize, plan, perform, and achieve goals as well as the capacity to flexibly adapt to changed circumstances (Diamond, 2013;Lezak, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, evidence has suggested the support of enhancing cognitive functioning in healthy older adults by using cognitive-based trainings (Gavelin et al, 2020;Sanjuán et al, 2020). Nevertheless, despite the diversity among applied cognitive interventions in healthy older adults, the VR-based intervention has not been widely adopted for boosting EFs (Kim et al, 2021). EFs (i.e., inhibitory control, WM, and attentional flexibility) has been linked with daily activities since these functions include the ability to evaluate, organize, plan, perform, and achieve goals as well as the capacity to flexibly adapt to changed circumstances (Diamond, 2013;Lezak, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…VR has several applications for improving (or training) older adults. Although exposure to VR application may result in symptoms of motion sickness for some people (e.g., eye fatigue, headaches, and nausea) (Park et al, 2019), its advantages include a secure environment, high ecological validity, and an inexpensive aid to support active aging (Appel et al, 2020;Kim et al, 2021;Syed-Abdul et al, 2019). A previous study revealed the acceptance (or positive perception) of older adults toward using VR (Mascret et al, 2020), namely, they perceived the VR to be useful, an enjoyable experience, and easy to use (Mascret et al, 2020;Syed-Abdul et al, 2019).…”
Section: R E S U M E Nmentioning
confidence: 99%
“…There are some potential limitations to be considered when interpreting the present findings. First, even though our sample size is larger than in most previous VR studies examining attentional-executive functions (see, e.g., Kim et al, 2021), it is somewhat limited considering the sampling distributions. Especially the age distribution in this sample is relatively narrow, and since the participants were recruited so that the families contacted us based on the advertisements, a sampling bias may be present.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…VR refers to digitally generated, immersive artificial environments. Today, VR-based neuropsychological research targeting, for example, attention, executive functions, and memory (see review by Kim et al, 2021) is being published at an accelerating rate (Krohn et al, 2020). In children, VR has been successfully used to implement conventional experimental tasks, such as a variant of the widely used Continuous Performance Test where the task is performed in a virtual classroom environment (see, e.g., Parsons & Rizzo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ways to seamlessly integrate the use of technology in older adults has been a topic of interest since the late 1980s [ 17 ]. More recently, VR use has been studied in cognitively impaired older adult population for neuropsychiatric testing [ 18 , 19 ], cognitive rehabilitation [ 20 ], and reducing neuropsychiatric symptoms associated with dementia [ 21 ]. Researchers have worked to find innovative ways to reduce neuropsychiatric symptoms in those diagnosed with dementia.…”
Section: Introductionmentioning
confidence: 99%